Optimization of media compositions for lipase production from coconut dregs by solid state fermentation - Nur Izzatul Akmar Muhammad Zaini (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
Lipase are enzymes which catalyze the hydrolysis of triglycedes. In this study, the lipase was produced by solid state fermentation (SSF) using Aspergillus niger. In this work, the waste from extraction of coconut milk which is coconut dregs was used as substrate and suplemented with nutriens and olive oil during fermentation. The aim of this research is to optimize media composition for lipase production byResponse Surface Methodology (RSM) , using Central Composite Design (CCD). The design was carried out to study the effect of parameters involved to obtain high production of lipase . In this study, concentration of carbon source (sucrose), nitrogen source (peptone) and inducer (olive oil) have being optimized.